1973
DOI: 10.1073/pnas.70.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Deoxynucleotidyl Transferase in a Case of Childhood Acute Lymphoblastic Leukemia

Abstract: Cells from a patient with childhood acute lymphoblastic leukemia contain an apparent DNA polymerase activity that was not found in any other cells except thymus cells. The enzyme has the properties of terminal transferase, an enzyme known to be found in thymocytes. The cells also contain the three major DNA polymerases found in growing cells. The results suggest that these tumor cells arose from a block in the differentiation of thymocytes. Terminal transferase may be a marker for the origin of leukemic cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
1

Year Published

1974
1974
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(55 citation statements)
references
References 21 publications
1
53
0
1
Order By: Relevance
“…One could imagine that malignant transformation had occurred in a pluripotential stem or early progenitor cell with production of multiple types of more differentiated cells in both the myeloid and lymphoid lines. Although transferase is normally present in high concentration only in thymus, its presence in hematopoietic cells of patient MR and children with acute lymphoblastic leukemia (4,5) suggests that lymphoid progenitor cells from bone marrow as well as thymocytes may contain transferase. The major reservoir of lymphoid progenitor cells in adults is thought to be bone marrow (17), an I such cells are probably rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could imagine that malignant transformation had occurred in a pluripotential stem or early progenitor cell with production of multiple types of more differentiated cells in both the myeloid and lymphoid lines. Although transferase is normally present in high concentration only in thymus, its presence in hematopoietic cells of patient MR and children with acute lymphoblastic leukemia (4,5) suggests that lymphoid progenitor cells from bone marrow as well as thymocytes may contain transferase. The major reservoir of lymphoid progenitor cells in adults is thought to be bone marrow (17), an I such cells are probably rare.…”
Section: Discussionmentioning
confidence: 99%
“…The unique localization of the transferase is of uncertain biological significance, but there are speculations that it may play a role in conveying immunological specificity (or immunological diversity) to T and possibly B lymphocytes during their differentiation (1,3,4). Demonstration of deoxyribonucleotidyl transferase activity in leukemic cells of certain children with acute lymphoblastic leukemia (5) and cell lines derived from patients with acute lymphoblastic leukemia (6) leads to the suggestion that malignant cells in acute lymphoblastic leukemia might arise from thymocytes or their precursors (5).…”
mentioning
confidence: 99%
“…Since the discovery of high TdT activity in blasts of an ALL case (McCaffrey et al, 1973) there have been many studies on this enzyme in leukaemia. Thus far, in most cases of ALL (Coleman et al, 1976;Greenwood et al, 1977), in about one third of cases with CML in blast crisis (Sarin et al, 1976;Sasaki & Sakamoto, 1977) and in a few cases with acute myelogenous leukaemia (AML) (Stass et al, 1979), high enzyme activities were reported.…”
mentioning
confidence: 99%
“…The enzyme is present in 1-5% of murine marrow cells (Pazmino et al, 1977) and is restricted to the immature cortisone-sensitive fraction of thymic lymphocytes. The enzyme has also been found in the cells of patients with non-T, non-B, acute lymphoblastic leukaemia (ALL), T-cell ALL, and of some patients with blast transformation of chronic granulocytic leukaemia (CGL), but is usually absent in other types of leukaemia (McCaffrey et al, 1973;1975;Coleman et al, 1974Coleman et al, , 1976Sarin et al, 1976;Hoffbrand et al, 1977). It appears therefore that the enzyme is present in the pluripotential marrow stem cell and is lost as cells mature down the myeloid or lymphoid pathways, being retained only in thymocytes.…”
mentioning
confidence: 99%